An experimental study of woody avoidance in Grasshopper sparrows (Ammodramus savannarum) - Anderson, Logan (My University, 2026)
Woody encroachment alters and fragments native prairies, and it is a major driver in global grassland loss and declines in the bird that depend on them. The presence of woody plants can increase nest predation risk, and many grassland birds appear to strongly avoid trees by altering their space use in the presence of woody plants. To understand why woody avoidance occurs in grassland birds, I hypothesized the behavior is driven by either by an innate fear shaped by an evolutionary history of elevated risk, or by current experience of predators encountered in encroached areas. To distinguish between these mechanisms, I experimentally manipulated woody plant presence and simulated predator risk. I used radio transmitters to track a common grassland songbird, the Grasshopper Sparrow (Ammodramus savannarum), in the Flint Hills of eastern Kansas, comparing unmanipulated periods as controls, after the introduction of experimentally placed trees, after the introduction of a decoy predator, and during a combination of trees and the predator decoy. Treatments were located around each sparrow’s territory center, and each bird was compared to its own control period. I measured the distance of each sparrow’s location to the center of its territory, its daily home range estimates, and the number of location estimates between 6-10 AM. Sparrows moved ~11 meters closer to the territory center during the predator treatment (p < 0.0001), ~4 meters closer during the tree treatment (p < 0.0001), and moved ~5 meters further away during the combination of the predator and tree (p = 0.0002). The home range area did not change over any of the treatments. The number of location estimates decreased during the cedar-only treatment (p < 0.0001) and the combined cedar-decoy shrike treatment (p < 0.0001), suggesting sparrows decrease their movements or hide during the treatments with trees. These results suggest that avoidance of woody plants are not due to elevated perceived predation risk but rather, due to an innate fear of woody plants themselves. Management should thus focus on the removal of encroaching woody plants rather than targeting the predators that may come with them. This study provides insights into the behavioral mechanisms leading to habitat selection in the face of a dire anthropogenic threat to Great Plains grassland-dependent birds.
Keywords: Movement ecology; Woody encroachment; Tallgrass prairie; Landscape of fear